Generalization in the Tropics – Development Policy, Randomized Controlled Trials, and External Validity - Peters, Jorg (Published by Oxford University Press on behalf of the World Bank, 2019)
When properly implemented, Randomized Controlled Trials (RCT) achieve a high degree of internal validity. Yet, if an RCT is to inform policy, it is critical to establish external validity. This paper systematically reviews all RCTs conducted in developing countries and published in leading economic journals between 2009 and 2014 with respect to how they deal with external validity. Following Duflo, Glennerster, and Kremer (2008), we scrutinize the following hazards to external validity: Hawthorne effects, general equilibrium effects, specific sample problems, and special care in treatment provision. Based on a set of objective indicators, we find that the majority of published RCTs does not discuss these hazards and many do not provide the necessary information to assess potential problems. The paper calls for including external validity dimensions in a more systematic reporting on the results of RCTs. This may create incentives to avoid overgeneralizing findings and help policy makers to interpret results appropriately.